Expert’s comment concerning Grand Rounds case entitled “The routine intra-operative use of pulse oximetry for monitoring can prevent severe thromboembolic complications in anterior surgery” (by M.A. König, Y. Leung, S. Jürgens, S. MacSweeney and B.M. Boszczyk) - Brau, Salvador A. (Springer-Verlag, 2011)
Routine monitoring of left extremity circulation with pulse oximetry during anterior lumbar surgery may help diagnose left iliac artery thrombosis and will lead to quick treatment of this potentially catastrophic complication.